Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Syntheses of 1,2-amino alcohols and their applications for oxazaborolidine catalyzed enantioselective reduction of aromatic ketones - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S. (Australian Journal of Chemistry, 2007)
Six new chiral 1,2-amino alcohol derivatives have been synthesized starting from (1R, 2R)-2-amino-1-phenylpropane-1,3- diol. Asymmetric reduction of aryl ketones with in-situ generated oxazaborolidine from these amino alcohol derivatives and BH3 center dot Me2S afforded secondary alcohols with good yield and moderate to high enantiomeric excess.

Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Synthesis of chimeric tetrapeptide-linked cholic acid derivatives: impending synergistic agents - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Dodd, Robert H.; Thierry, Josiane; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit (Bioorganic & Medicinal Chemistry Letters, 2008)
Tetrapeptides derived from glycine and beta-alanine were hooked at the C-3 beta position of the modified cholic acid to realize novel linear tetrapeptide-linked cholic acid derivatives. All the synthesized compounds were tested against a wide variety of microorganisms (Gram-negative bacteria, Gram-positive bacteria and fungi) and their cytotoxicity was evaluated against human embryonic kidney (HEK293) and human mammary adenocarcinoma (MCF-7) cell lines. While relatively inactive by themselves, these compounds interact synergistically with antibiotics such as fluconazole and erythromycin to inhibit growth of fungi and bacteria, respectively, at 1-24 mu g/mL. The synergistic effect shown by our novel compounds is due to their inherent amphiphilicity. The fractional inhibitory concentrations reported are comparable to those reported for Polymyxin B derivatives. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial activity; Cholic acid; Cytotoxicity; Synergism; Tetrapeptide

Stereoselective construction of steroidal side chain from 16-dehydropregnenolone acetate - Aher, Nilkanth G.; Gonnade, Rajesh G.; Pore, Vandana S. (Synlett, 2009)
Stereoselective construction of steroidal side chain at C-20 having `natural' configuration using 16-dehydropregnalone acetate (16-6PA) as a starting material has been carried out. Palladium-catalyzed carbon-carbon bond-forming Heck reaction between C-20 vinyl iodide with methyl acrylate and transfer hydrogenation with triethylsilane and Pd/C are the key steps for stereoselective side-chain synthesis.
Keywords: 16-dehydropregnenolone acetate; Heck coupling; stereoselectivity; steroidal side chain; transfer hydrogenation

Synthesis and antifungal activity of 1,2,3-triazole containing fluconazole analogues - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Kumar, Awanit; Shukla, Praveen K.; Sharma, Aanchal; Bhat, Manoj K. (Bioorganic & Medicinal Chemistry Letters, 2009)
Fluconazole based novel mimics containing 1,2,3-triazole were designed and synthesized as antifungal agents. Their antifungal activities were evaluated in vitro by measuring the minimal inhibitory concentrations (MICs). Compounds 12, 15, and 16 were found to be more potent against Candida fungal pathogens than control drugs fluconazole and amphotericin B. The studies presented here provide structural modi. cation of fluconazole to give 1,2,3-trazole containing molecules. Furthermore, these molecules were evaluated in vivo against Candida albicans intravenous challenge in Swiss mice and antiproliferative activities were tested against human hepatocellular carcinoma Hep3B and human epithelial carcinoma A431. It was found that compound 12 resulted in 97.4% reduction in fungal load in mice and did not show any profound proliferative effect at lower dose (0.001 mg/ml). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Conjugates; Fluconazole

Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones

Synthesis and antifungal activity of 1,5-disubstituted-1,2,3-triazole containing fluconazole analogues - Pore, Vandana S.; Jagtap, Manisha A.; Agalave, Sandip G.; Pandey, Atindra K.; Siddiqi, Mohammad I.; Kumar, Vikash; Shukla, Praveen K. (Medchemcomm, 2012)
Fluconazole based novel mimics containing 1,5-disubstituted 1,2,3-triazoles were synthesized by using Ru catalysed 1,3 dipolar cycloaddition. All the newly synthesized compounds and pure enantiomers were more potent than fluconazole against Candida albicans. Docking of 9A and 9B showed different conformation in the active site of Cyp51 of Candida albicans. The more active compounds 2 and 2A did not exhibit any toxicity up to 3.12 mu g mL(-1) against mammalian cell line L929.

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.